Increased Body Mass Index may lead to Hyperferritinemia Irrespective of Body Iron Stores - Alam, Faiza (Pak J Med Sci, 2015)
OBJECTIVE: Obesity causes subclinical inflammation which results in the secretion of various bioactive peptides that are key players in metabolic regulation of iron homeostasis. We sought to establish correlation of one such peptide (ferritin) with marker of subclinical inflammation (CRP) in various BMI. METHODS: Total 150 subjects between the ages of 20-60 years were included in the cross-sectional study conducted at Basic Medical Sciences Institute, Jinnah Post Graduate Medical Centre, Karachi, Pakistan. Body Mass Index (BMI) was calculated by weight (kg) /height (m(2)). The given values were used as reference for Group A: normal weight (18.0-22.9 kg/m2), Group B: overweight (23.0-24.9 kg/m2), Group C: obese (>25.0 kg/m2) according to South Asian criteria. Serum Iron, Total Iron Binding Capacity, serum Transferrin Saturation, serum Ferritin and C-reactive protein were measured by commercially available kits. ANNOVA with Tukey’s minimum significant difference and Spearman Rho correlation were used considering p<0.05 significant. RESULTS: The results identified an increased serum Ferritin and CRP in obese versus lean subjects (p < 0.001). BMI showed significantly positive correlation with serum CRP (r = 0.815; p-value < 0.01) and Ferritin (r = 0.584; p-value < 0.01). However, serum Iron levels and Transferrin saturation decreased in obese versus normal weight individuals (p < 0.001). CONCLUSION: This integrated new data reveals that individuals with high BMI had high levels of Serum Ferritin despite low levels of iron with high levels of C- reactive protein. This might be caused due to inflammatory conditions prevailing in the presence of increased adipose tissue.